Implementasi Bak Sampah Otomatis Berbasis Mikrokontroler Untuk Mendukung Efisiensi Kerja Pada Salah Satu UMKM Di Desa Lendang Nangka - sulthoni, Adriyan; Purnama, Alfhat Diya (International Journal of Science, Technology and Applications, 2023)
Efficient waste management is a challenge for many SMEs, including iced tea businesses, in maintaining cleanliness and operational comfort. This research aims to design and implement a microcontroller-based automatic trash bin system as an innovative solution for waste management. The researchers focus on utilizing Arduino microcontroller technology with ultrasonic sensors to detect objects automatically. This study addresses the fundamental question of how an automated system can enhance waste management efficiency through prototype design and testing. The system successfully opens and closes the trash bin lid automatically with a fast response time, minimizing direct user interaction with the bin. Findings indicate that this system improves cleanliness, reduces the risk of germ transmission, and has potential for further development, such as adding waste capacity sensors and mobile application integration. Thus, this system offers an efficient and cost-effective solution for waste management at the SME scale.